Analysis of Cognitive Learning Strategies Focused on the Acquisition of Information in Elementary School Students - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This article analyzes the cognitive learning strategies focused on information acquisition used by secondary school students, aiming to identify the levels of appropriation and effectiveness in the learning process. The research, based on a quantitative descriptive design, was conducted with a sample of 150 secondary school students from an educational institution in Montería, Colombia. The ACRA questionnaire, designed to evaluate cognitive learning strategies, was used as the primary data collection instrument. The results indicate that information acquisition strategies, such as rehearsal and information organization, are used with moderate frequency, suggesting a partial application of deep learning processes. The need to strengthen training in learning techniques focused on self-regulation and active information processing is highlighted. The findings provide valuable insights for the implementation of pedagogical interventions aimed at improving academic performance and student autonomy.